The role of Tivumbeni College as a centre of professional development of educators in the Ritavi District between 2000 and 2002 - Maluleke, Samuel Maselesele (My University, 2003)
Refer to document
Thesis (M. Dev.) -- University of Limpopo, 2003
Keywords: Professinal development; Teacher's training; Career development -- South Africa; Vocational education -- South Africa; Teachers -- In-service training; Teacher centers